Pengembangan Objek Wisata Gua Popogu Desa Sangowo Barat, Kabupaten Pulau Morotai - Samili, Asnita Ode; Hasim, Jainudin; Sibua, Ahmad (Universitas Khairun, 2024)
This study was conducted to determine the development of the Popogu Cave tourist attraction in Sangowo Barat Village, East Morotai District, Morotai Island Regency. The subjects of this study were the Head of Sangowo Barat Village, the owner of the Popogu Cave tourist attraction land, Bumdes Sangowo Barat, the people of Sangowo Barat Village and visitors to the Popogu Cave tourist attraction, who were made the subjects of the study as many as eighteen people. The research method used was a qualitative descriptive method. Based on the research data, it shows that in the interview results regarding the development of the Popogu Cave tourist attraction in Sangowo Barat Village, it can be seen from three aspects, namely management, form of development, inhibiting factors. In the management of the availability of facilities at the Popogu Cave tourist attraction, it is still very limited, therefore, it has not been managed properly, then the form of development still maintains its natural beauty so that sustainable development has not been carried out optimally, while the inhibiting factors are the lack of attention from related agencies and have not made improvements to accessibility to the location of the Popogu Cave tourist attraction in Sangowo Barat Village, East Morotai District, Morotai Island Regency.